2013
DOI: 10.3389/fpsyg.2013.00525
|View full text |Cite
|
Sign up to set email alerts
|

(A)musicality in Williams syndrome: examining relationships among auditory perception, musical skill, and emotional responsiveness to music

Abstract: Williams syndrome (WS), a genetic, neurodevelopmental disorder, is of keen interest to music cognition researchers because of its characteristic auditory sensitivities and emotional responsiveness to music. However, actual musical perception and production abilities are more variable. We examined musicality in WS through the lens of amusia and explored how their musical perception abilities related to their auditory sensitivities, musical production skills, and emotional responsiveness to music. In our sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 79 publications
2
49
0
Order By: Relevance
“…Mean scores for each group are shown in As previously mentioned (see section 1.4. Studies of musical pitch in Williams syndrome), the prevalence rate of amusia in individuals with WS is higher than that in the TD population (Lense et al, 2013). As shown in Figure 2, in this study no participant with WS performed at floor.…”
Section: Development Of Pitch-related Music Skills In Ws 17mentioning
confidence: 47%
See 4 more Smart Citations
“…Mean scores for each group are shown in As previously mentioned (see section 1.4. Studies of musical pitch in Williams syndrome), the prevalence rate of amusia in individuals with WS is higher than that in the TD population (Lense et al, 2013). As shown in Figure 2, in this study no participant with WS performed at floor.…”
Section: Development Of Pitch-related Music Skills In Ws 17mentioning
confidence: 47%
“…Interestingly, a moderate association between performance on the music test and cognitive level was observed. More importantly, Lense et al (2013) found a higher rate of amusia in WS compared with typical development. Yet, the neural correlates of amusia are similar in both populations (Lense, Dankner, Pryweller, Thornton-Wells, & Dykens, 2014).…”
Section: Studies Of Musical Pitch In Williams Syndromementioning
confidence: 86%
See 3 more Smart Citations